Seasonal variations of soil moisture regime at dry region of lowland dipterocarp forest in Pasoh forest reserve, Peninsular Malaysia - Badaluddin, Noor Atiqah; Lion, Marryanna; Mohd Razali, Sheriza; Khalit, Saiful Iskandar (Innovative Scientific Information and Services Network, 2021)
Soil moisture is an essential component in the terrestrial hydrological process and greatly influences nutrient cycle and energy flow. Tropical rainforest sometimes experiences a severe dry period for several months. Soil moisture is responsible for regulating transpiration during this time. This study focuses on the soil moisture in the tropical rainforest by determining soil water content at 6 ha Pasoh Reserve Forest, Negeri Sembilan, Peninsular Malaysia. The study area is located within the drier area in Peninsular Malaysia and therefore is suitable for assessing soil moisture fluctuation during the dry and wet seasons. We measure soil moisture from 39 grid points using Amplitude Domain Reflectometry (ADR-type) soil moisture profile probe from a different soil depth at 0.1, 0.2, 0.3, 0.4, 0.6 and 1.0 meter monthly. This study aims to determine the seasonal soil moisture fluctuation in the Pasoh Forest Reserve as the effect of monsoon season. During the Northeast monsoon season between October 2019 to March 2020, soil water content was higher than the other months of the year. October shows the most rainfall, amounting 364.77 mm month-1. Expectedly, at all soil depth, the moisture revealed the higher as the rain is at most. The soil moisture also increased significantly with a deeper soil depth at 1m, compared to shallower soil depth. This study could be used as a model for developing forests associated with soil moisture and the ecological character of the tropical forest.